Integrating Video Scribe and Problem-Based Learning: A Development Study to Foster Elementary Students’ Conceptual Understanding in Natural and Social Sciences - Siti Nur Syamsiah; Aan Hendrayana; Suroso Mukti Leksono (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and implement VideoScribe-based learning media integrated with the Problem-Based Learning (PBL) model to improve students’ conceptual understanding in Natural and Social Sciences (IPAS) at the elementary school level. Employing a Research and Development (R&D) approach based on the ADDIE model, the study involved 20 fourth-grade students selected through purposive sampling at SDN Tanjungan 1. The students participated in a small-scale pilot evaluation as part of the implementation phase of the ADDIE model to assess the feasibility and practicality of the VideoScribe-based learning media prior to broader implementation. Data were collected through observations, interviews, pretests and posttests, questionnaires, and documentation, and were analyzed using qualitative and quantitative techniques, including descriptive statistics and the N-Gain formula. The results showed that the developed media achieved an overall feasibility score of 86.3%, indicating a high level of validity across the material, media, and language aspects. Furthermore, students’ conceptual understanding improved, as reflected in the increase in the mean score from 48.20 on the pretest to 84.10 on the posttest, with the N-Gain falling within the moderate-to-high category. These findings suggest that integrating VideoScribe-based learning media with the PBL model has the potential to enhance students’ learning outcomes. The study contributes to the growing body of literature by providing empirical evidence that aligning multimedia tools with student-centered pedagogical models can support the development of students’ conceptual understanding. It also offers practical implications for teachers seeking to design more interactive, contextualized, and meaningful learning environments, particularly in elementary education contexts.